Reduced live birth rates in frozen versus fresh single cleavage stage embryo transfer cycles: A cross -sectional study - Wan Tinn Teh; Alex Polyakov; Claire Garrett; David Edgar; John Mcbain; Peter Adrian Walton Rogers (Shahid Sadoughi University of Medical Sciences, 2020)
Background: Studies have suggested that embryo-endometrial developmental asynchrony caused by slow-growing embryos can be corrected by freezing the embryo and transferring it back in a subsequent cycle. Therefore, we hypothesized that live birth rates (LBR) would be higher in frozen embryo transfer (FET) compared with fresh embryo transfers. Objective: To compare LBR between fresh and FET cycles. Materials and Methods: A cross-sectional analysis of 10,744 single autologous embryo transfer cycles that used a single cleavage stage embryo was performed. Multivariate analysis was performed to compare LBR between FET and fresh cycles, after correcting for various confounding factors. Sub-analysis was also performed in cycles using slow embryos. Results: Both LBR (19.13% vs 14.13%) and clinical pregnancy (22.48% vs 16.25%) rates (CPR) were higher in the fresh cycle group (p < 0.00). Multivariate analysis for confounding factors also confirmed that women receiving a frozen-thawed embryo had a significantly lower LBR rate compared to those receiving a fresh embryo (OR 0.76, 95% CI 0.68-0.86, p < 0.00). In the sub-analysis of 1,154 cycles using slow embryos, there was no statistical difference in LBR (6.40% vs 6.26%, p = 0.92) or CPR (8.10% vs 7.22%, p = 0.58) between the two groups. Conclusion: This study shows a lower LBR in FET cycles when compared to fresh cycles. Our results suggest that any potential gains in LBR due to improved embryo-endometrial synchrony following FET are lost, presumably due to freeze-thaw process-related embryo damage.